Development of an orally bioavailable stress kinase inhibitor with brain exposure that targets the neuroinflammation‐synaptic dysfunction pathophysiology axis: Human/Human trials: Other. (7th December 2020) - Watterson, Daniel Martin; Arancio, Ottavio; Windisch, Manfred; Pelletier, Jeffrey; Roy, Saktimayee M.
Abstract: Background: An ambitious primary goal of NAPA is to identify disease modifying interventions, a goal complicated by the nearly complete failure of all clinical trials. However, a common yet neglected target is the pathophysiology progression theme of synaptic dysfunction associated with aspects of neuroinflammation that contribute to synaptic dysfunction. The neuroinflammation‐synaptic dysfunction hypothesis posits that certain aspects of this axis are amenable to therapeutic intervention. The druggable stress kinase p38αMAPK is a key target in the neuroinflammation‐synaptic dysfunction pathophysiology progression axis. Increased activity in activated glia results in dysregulated innate immunity as evidenced by increased levels of proinflammatory cytokines. Increased activity in neurons results in altered axonal transport and synaptic dysfunction. Neuronal dysfunction, in turn, results in further stimulation of the evolving stress cycle. Concurrent inhibition of the single target p38αMAPK in distinct cells of the pathophysiology axis could provide a novel form of potential pleiotropic intervention with increased potential for efficacy. Method: A fragment‐based, secondary pharmacology‐filtered experimental approach allowed the custom design and production of a novel p38αMAPKI drug candidate, MW150 (= MW01‐18‐150SRM), with exceptional molecular selectivity and concurrent avoidance of dose limiting barriers identified in prior clinical candidates. IND‐enabling preclinical toxicology integrated with preclinical pharmacokinetics and pharmacodynamics documented a potential for first‐in‐human clinical evaluation (summarized in Roy, S. M., et al., 2019, J.Med.Chem ., Drug Annotation: A Selective and Brain Penetrant p38αMAPK Inhibitor Candidate for Neurologic and Neuropsychiatric Disorders That Attenuates Neuroinflammation and Cognitive Dysfunction) Result: MW150 is a unique, orally bioavailable, stress kinase inhibitor that exhibits brain exposure and efficacy in diverse CNS disease models characterized by a neuroinflammation‐synaptic dysfunction axis. Promising results from ongoing studies suggest MW150 may be phase 2‐ready clinical asset available in Q3 2020: 1) phase 1a (SAD) and 1b (MAD) clinical trials; 2) six‐ and nine‐month preclinical toxicology; 3) commercial scale GMP clinical drug suitable for phase 2 and 3 clinical trials. Conclusion: MW150 has the potential to provide a new therapeutic intervention mechanism for neurologic disease modification. There are no clinical trials of drugs with MW150's unique profile of molecular recognition, pharmacological selectivity and safety.